2013
DOI: 10.1002/cctc.201300220
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Pd‐Catalyzed CH Oxidative Cyclization of Homoallylhydrazones to Pyrazolines and Tetrahydropyridazines

Abstract: Pd‐catalyzed 5‐exo‐trig or 6‐endo‐trig CH oxidative cyclization of C‐homoallyl‐N‐sulfonylhydrazones to 5‐vinylpyrazolines or 6‐methylidene‐1,4,5,6‐tetrahydropyridazines, respectively, is shown to be controlled in a highly selective manner by the ionic character of the PdII catalytic center. This character is ultimately defined by the nature of the X ligand in the PdX2 salt serving as an in situ precursor of the active catalytic species involving BIPHIMIP {2‐(diphenylphosphino)‐1‐[2‐(diphenylphosphino)phenyl]‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In this context, hydrazones represent an appealing alternative, [21][22][23][24] being easy to prepare and displaying a very peculiar reactivity. [25][26][27][28][29][30] Many synthetic approaches exploiting them have been reported, like Palladium 31,32 and Copper mediated cyclizations, 33,34 but especially, visible light-mediated processes. Photocatalytic transformations have, indeed, attracted huge interest in the last years, disclosing alternative routes to functionalized molecules under mild reaction conditions and with high functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, hydrazones represent an appealing alternative, [21][22][23][24] being easy to prepare and displaying a very peculiar reactivity. [25][26][27][28][29][30] Many synthetic approaches exploiting them have been reported, like Palladium 31,32 and Copper mediated cyclizations, 33,34 but especially, visible light-mediated processes. Photocatalytic transformations have, indeed, attracted huge interest in the last years, disclosing alternative routes to functionalized molecules under mild reaction conditions and with high functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, many efforts have been dedicated to new strategies for the construction of these nitrogen heterocycles: among those are [4 + 2] cycloaddition of azoalkenes, 1,2-diaza-1,3-dienes, , or diazenes, and [3 + 3] formal cycloadditions exploiting cyclopropyl derivatives and hydrazones. , Nevertheless, the need for available starting materials and a good compatibility of reaction conditions with several functional groups has been the driving force for the use of other cyclization strategies. In this context, hydrazones represent an appealing alternative, being easy to prepare and displaying a very peculiar reactivity. Many synthetic approaches exploiting them have been reported, like palladium , and copper mediated cyclizations, , but especially visible light-mediated processes. Photocatalytic transformations have, indeed, attracted huge interest in the past years, disclosing alternative routes to functionalized molecules under mild reaction conditions and with high functional group tolerance. In particular, visible light-mediated generation of N -centered radicals , has rapidly become one of the most efficient approaches in the synthesis of N -heterocycles (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar products, though not optically active and containing an exocyclic alkenyl group, can be obtained at moderate to good yields using 1,4‐benzoquinone as the oxidant and a diphosphine ligand, starting from γ , δ ‐unsaturated hydrazones 254 (Scheme 52). The authors observed that in the presence of para ‐toluene sulfonic acid (PTSA), the expected pyrazolines 255 were formed via a 5‐ exo‐trig process, whereas in the absence of PTSA, the six‐membered tetrahydropyridazines were formed as a result of 6‐ endo‐trig transformation [81] …”
Section: Intramolecular Cyclizations Of Unsaturated Hydrazonesmentioning
confidence: 99%
“…The authors observed that in the presence of para-toluene sulfonic acid (PTSA), the expected pyrazolines 255 were formed via a 5-exo-trig process, whereas in the absence of PTSA, the six-membered tetrahydropyridazines were formed as a result of 6-endo-trig transformation. [81] Alternatively, as Wang and Han describe, an additional alkene can be used to insert an alkenyl group at C-5 of the pyrazoline ring. Specifically, β,γ-unsaturated hydrazones 256 can successfully react with bromoal-Scheme 50.…”
Section: Palladium-catalyzed Cyclizationsmentioning
confidence: 99%